(untitled) (Existential Analysis: Journal of the Society for Existential Analysis, 2012)
We examined relationships between personality characteristics and death awareness in a graduate student sample. 72 students completed a personality measure, ruminated about their death (n = 36) or dental pain (n = 36), and then completed a death-thought accessibility measure. Findings revealed a significant positive association between level of neuroticism and death awareness regardless of whether or not they were primed to think about death. Implications for theory and practice are discussed.